PROBLEMS ASSOCIATED WITH THE SOKH RIVER ENTERING FROM NEIGHBORING COUNTRIES, ITS HYDROGRAPHIC CONDITIONS, AND THE STUDY OF HEAVY METAL CONTENT IN ITS WATERS BEYOND MERCURY - Bazarov Abdurasul Abdusamatovich (Modern American Journals, 2025)
This article mainly examines the formation of the Sokh River, its relationship with groundwater, the influence of tributaries on the river’s formation, and the major problems associated with the Sokh River. In addition, the hydrographic conditions of the Sokh River and information on heavy elements transported by the river, including heavy metals other than mercury, are presented. The study focuses on the composition of river flows and the environmental challenges related to transboundary water resources.
Keywords: Sokh River, groundwater, problems, hydrographic conditions, water abundance, flow composition, heavy elements.